Eksorsisme dalam Perspektif Gereja Katolik - Herianto, Tjatur (Perspektif, 2020)
The article describes that the practice of exorcism in the Catholic Church is very rare. However, when the presence of Satan or Demon appears clearly in attacking human life and deforming it physically, it is considered acceptable that exorcism has to be put into practise. The writer argues that in the Catholic Church any case of exorcism must pass through a meticuluous and extra examination. An exorcist has also to follow a strict regulation of the Church and be equipped with special trainings; otherwise he or she could be severely sanctioned. On the other hand, the Church has to remain vigilant to face any dark forces with Christian faith in the power of Jesus Christ as well as to the rationality of our today’s modern world.